Peningkatan Kemampuan Komunikasi MatematikaMelalui Pendekatan Pembelajaran Matematika Realistik - Kurniawan, Edi, Drs Slamet HW .M.Pd (2017)
ABSTRACT The background of this research, lack of communication skills in mathematics. Aiming to describe the application of mathematics learning approach Realistikdalam learning, to improve mathematical communication skills through learning approach Realistic Mathematics in the learning of mathematics. The study design, classroom action research conducted in collaboration between researchers and teachers in class VIII, which is conducted in two cycles. The research subjects, the class teacher of SMP NU 1 Wonosegoro as subjects giver action, class VIII A total of 32 people as the subject of the recipient action. Data collection techniques, there are four methods of documentation, interviews, observation and field notes. The results showed an increase in students' mathematical communication skills through realistic mathematics learning approach. This proved an increased ability to ask before action 40.625%, after the act of the first cycle to 53.125%, and after the second cycle reach 84.375%. Ability ask and answer questions, before action is only 28.125%, after the first cycle to 46.875%, and after the second cycle reach 78.375%. Ability mengemukaka idea / ideas before action 34.375% following the actions of the first cycle to 59.375% and after the second cycle of around 75%. Ability mempersentasikan results, before action is only 15.375%, after the first cycle to 4.375% after the second cycle reach 71.875%. Based on these results the researchers conclude that learning using realistic mathematics learning approach capable of improving the communication skills of mathematics students on material cubes and blocks. Keywords: mathematical communication skills, realistic approach to learning mathematics